2012
DOI: 10.1111/j.1464-410x.2011.10860.x
|View full text |Cite
|
Sign up to set email alerts
|

Diet and its role in interstitial cystitis/bladder pain syndrome (IC/BPS) and comorbid conditions

Abstract: What ' s known on the subject? and What does the study add? Nearly 90% of patients with interstitial cystitis/bladder pain syndrome (IC/BPS) report sensitivities to a wide variety of dietary comestibles. Current questionnaire-based literature suggests that citrus fruits, tomatoes, vitamin C, artifi cial sweeteners, coffee, tea, carbonated and alcoholic beverages, and spicy foods tend to exacerbate symptoms, while calcium glycerophosphate and sodium bicarbonate tend to improve symptoms. At present we recommend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(58 citation statements)
references
References 58 publications
1
54
0
1
Order By: Relevance
“…15,59 Based on survey studies, common food triggers include coffee, tea, citrus fruits, carbonated and alcoholic beverages, bananas, tomatoes, spicy foods, artificial sweeteners, vitamin C, and wheat products. 15,59,60 Only one placebo-controlled, randomized, controlled trial (RCT) on the effect of diet in IC/BPS has been published, which failed to report any significant association. 61 Dietary modifications, such as a steady intake of water to dilute urine and reduce constipation, 62 and an elimination diet trial have been advocated.…”
Section: Patient Education (Recommended In All Patients Grade A) Andmentioning
confidence: 99%
See 1 more Smart Citation
“…15,59 Based on survey studies, common food triggers include coffee, tea, citrus fruits, carbonated and alcoholic beverages, bananas, tomatoes, spicy foods, artificial sweeteners, vitamin C, and wheat products. 15,59,60 Only one placebo-controlled, randomized, controlled trial (RCT) on the effect of diet in IC/BPS has been published, which failed to report any significant association. 61 Dietary modifications, such as a steady intake of water to dilute urine and reduce constipation, 62 and an elimination diet trial have been advocated.…”
Section: Patient Education (Recommended In All Patients Grade A) Andmentioning
confidence: 99%
“…No standardized protocol exists, but common practice is to instruct patients to avoid all foods on the list for a period varying from one week to three months and then methodically re-introduce one item at a time, with a waiting period of three days to identify potential offenders. 60,62 …”
Section: Patient Education (Recommended In All Patients Grade A) Andmentioning
confidence: 99%
“…The therapies most often used by clinicians are usually generic and funding for evaluating such treatments is almost non-existent. Some of the best approaches include conservative management such as diet manipulation 8 , exercise 9 , improving coping skills and even cognitive behavioural therapy 9 ; all treatments never rigorously evaluated. One recent exception is pelvic floor physiotherapy in which the benefits suggested by early small uncontrolled studies have now been confirmed by NIH randomized controlled trials.…”
Section: Cuaj -Original Researchmentioning
confidence: 99%
“…Other chronic conditions often accompany IC/BPS, such as irritable bowel syndrome (IBS), fibromyalgia, and chronic fatigue syndrome. 12,13 Many patients with IC/BPS struggle with constipation. 14 Pelvic floor dysfunction, vulvodynia, and sexual dysfunction are frequent in this population.…”
Section: Overview Of Icmentioning
confidence: 99%